POST-CRISIS HOUSING MARKET PROBLEMS - A. L. Sadikov; T. A. Semina; A.V. Chernov (Модернизация, инновация, развитие, 2016)
At present, Russian housing market is characterized, on one hand, with acute shortage of dwellings for absolute majority of the population and on the other hand, with existence of many obstacles that block the market to develop so as to solve this problem. Housing market development trends are discussed along with due consideration of the state housing policy. There are several main directions of this development: increasing scope of little-story and economy class buildings, increased use of resource-saving technologies and widening the practice of public-private partnership. At the same time, state financial support to housing construction is planned to get gradually decreased.